THE IMPACT OF STUDENTS’ SECONDARY SCHOOL BACKGROUND IN SHORTHAND AND TYPEWRITING ON THEIR PERFORMANCE AT THE NIGERIA CERTIFICATE IN EDUCATION (NCE) LEVEL - Ibrahim, Sani (Sokoto Educational Review, 2020)
The researcher suspects that most of the students who encounter difficulties in the study of shorthand and typewriting at the NCE level have poor or no secondary school background in these subjects. The paper investigates the impact of students’ secondary school background in shorthand and typewriting on their performance in the subjects at the NCE level. The Z statistic was used in analysing the data collected. The result reveals that there is significant difference in the performance of students with and those without secondary school background in shorthand and typewriting in the subjects at the NCE level. Four recommendations were made. One of them is that the National Commission for Colleges of Education (NCCE) should amend its entry requirements into business education programs of colleges of education for those students who wish to eventually specialise in office/secretarial education to include credit in both shorthand and typewriting at the ordinary level.